1986
DOI: 10.2307/1938503
|View full text |Cite
|
Sign up to set email alerts
|

A 6000‐Year Record of Forest History on Mount Rainier, Washington

Abstract: Sediments in three ponds between 1300—1500 m on the south side of Mt. Rainier were examined for plant macrofossils and pollen. Macrofossils of seral species such as Abies lasiocarpa, Pseudotsuga menziesii, Pinus monticola, Abies procera, and Pinus contorta are conspicuous from 6000 to 3400 BP. These species suggest a climate that was warmer/drier than today and favored frequent fires. Neoglacial cooling may have begun 3700—3400 BP, as species typical of higher elevations became prominent; a decline in seral sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Plant macrofossils in sediments of small lakes generally represent trees growing within 10 0 -10 1 meters of the lake margin [17,58]. Such spatial precision has considerable advantages in application, but it also ensures that only a small number of individual trees are likely to be represented in a macrofossil assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…Plant macrofossils in sediments of small lakes generally represent trees growing within 10 0 -10 1 meters of the lake margin [17,58]. Such spatial precision has considerable advantages in application, but it also ensures that only a small number of individual trees are likely to be represented in a macrofossil assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…On Mt. Rainier, for example, Dunwiddie (1986) demonstrated that fires that occurred during the mid-1800s burned through an Abies amabilis and Tsuga mertensiana forest that had persisted for centuries. The mid-1800s were characterized by warming temperatures that caused earlier seasonal snowmelt and longer growing seasons.…”
Section: Crown Fire Dynamics In a Changing Climatementioning
confidence: 99%
“…These climate conditions allowed Tsuga heterophylla to become abundant briefly after the fires, and T. heterophylla was then replaced by A bies lasiocarpa. Because long-lived mature trees may survive short-term climate fluctuations, species that are best adapted to the current climate may only be able to enter the forest in open habitats following severe fires, and forest composition may respond to climatic changes primarily after disturbance (Dunwiddie 1986). A study by Cwynar (1987) also suggests that, although the ultimate cause of postglacial vegetation change in the Pacific Northwest was climate change, the proximate cause of some postglacial vegetation changes was an altered fire regime.…”
Section: Crown Fire Dynamics In a Changing Climatementioning
confidence: 99%
“…Empirical evidence was invoked by some other panelists to support the contrasting view, that succession after disturbance is unpredictable. One panelist drew on paleoecological evidence from Mount Rainier in the Pacific Northwest of the United States (Dunwiddie 1986) suggesting that climate change has altered the regeneration niche for tree species so that a disturbance event ''flipped'' the forest system to a completely new species assemblage.…”
Section: Nonlinear Development and Uncertaintymentioning
confidence: 99%